Effect of zinc ion concentration on crosslinking of carboxymethyl cellulose sodium-fumaric acid composite hydrogel. (26th May 2021) - Uyanga, Kindness A.; Iamphaojeen, Yuwanda; Daoud, Walid A.
Abstract: Anionic polysaccharides are known to react in unconventional patterns with di-valent metal ions to form 3D-structured hydrogels. However, little is known about the influence of divalent ions concentration on hydrogel formation. Herein, carboxymethyl cellulose based hydrogels crosslinked with zinc ions (Zn 2+ ) and fumaric acid are synthesized and characterized for swelling, structure, morphology and thermal properties, and the effect of Zn 2+ concentration on hydrogel properties is investigated. It was found that increasing Zn 2+ to 0.5 M enhances gel fraction and water absorbency, at which super-absorbent yet stable, crystalline (79% crystallinity index) FA-0.5 exhibiting water-absorbency (2259%) and stability toward water (51%) and heat (−3.17 mW and 0.9% degradation at 50 °C) is formed. The results reveal that crosslinking is influenced by Zn 2+ concentration and interaction with other hydrogel components. The hydrolytic and thermal properties of FA-0.5 shows potential as a stable biomaterial. Graphical abstract: Image 1 Highlights: CMC-Zn 2+ hydrogels are developed using naturally occurring materials. Tuning the zinc ions concentration affects hydrogel microstructure and stability. The optimal hydrogel structure provides controlled hydrolytic and thermal stability. The hydrogels are stable host matrices for a wide range of wearable applications.